Respostas
respondido por:
122
istema: x=3y x-2y=3
3y-2y=3
y=3
x=3.3
x=9
respondido por:
78
Sistema:
x = 3y
x - 2y = 3 Método da substituição, se x = 3y, podemos substituir na de baixo.
=> x - 2y = 3 x = 3y
3y - 2y = 3
y = 3
Com o valor de "y", vamos calcular "x".
Sabemos que:
x = 3y, Então =>
x = 3y
x = 3.3
x = 9
Solução = {9; 3}
x = 9 e y = 3
x = 3y
x - 2y = 3 Método da substituição, se x = 3y, podemos substituir na de baixo.
=> x - 2y = 3 x = 3y
3y - 2y = 3
y = 3
Com o valor de "y", vamos calcular "x".
Sabemos que:
x = 3y, Então =>
x = 3y
x = 3.3
x = 9
Solução = {9; 3}
x = 9 e y = 3
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás